2010
DOI: 10.1111/j.1541-4337.2010.00115.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Analysis: Relevance for Prebiotic, Probiotic, and Synbiotic Product Development

Abstract: Sensory analysis represents a decisive step during the various stages of food product development. For probiotic, prebiotic, and synbiotic foods, which have shown continuous and significant consumption in the functional food category, the choice of an appropriate technique allows obtaining relevant sensory information that contributes to consumer acceptance. This review focuses on the importance of sensory analytical techniques in prebiotic and probiotic food product development. Examples of the most known sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
96
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(112 citation statements)
references
References 143 publications
5
96
1
4
Order By: Relevance
“…Inulin added as powder tends to increase the hardness of meat products, whereas when added as a gel, it gives softer products. Texture modifi cation through the use of diff erent forms of inulin inclusion in a range of meat products is well documented in the literature (Alvarez and Barbut, 2013;Cegiełka and Tambor, 2012;Cruz et al, 2010;Keenan et al, 2014;Ktari et al, 2014;Menegas et al, 2013;Méndez-Zamora et al, 2015). In this study, inulin gel was used, and this can explain the decreased hardness and chewiness of the pâtés with Means ±standard deviation in the same row followed by diff erent lowercase letters indicates signifi cant diff erences (p < 0.05) among formulations (n = 30).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Inulin added as powder tends to increase the hardness of meat products, whereas when added as a gel, it gives softer products. Texture modifi cation through the use of diff erent forms of inulin inclusion in a range of meat products is well documented in the literature (Alvarez and Barbut, 2013;Cegiełka and Tambor, 2012;Cruz et al, 2010;Keenan et al, 2014;Ktari et al, 2014;Menegas et al, 2013;Méndez-Zamora et al, 2015). In this study, inulin gel was used, and this can explain the decreased hardness and chewiness of the pâtés with Means ±standard deviation in the same row followed by diff erent lowercase letters indicates signifi cant diff erences (p < 0.05) among formulations (n = 30).…”
Section: Resultsmentioning
confidence: 93%
“…Alvarez and Barbut (2013) found that fat reduction in cooked pork batters from 20% to 5% brought about a 35% decrease in hardness, and other parameters of texture. According to Cruz et al (2010), the addition of inulin signifi cantly aff ects the texture of products, because it is incorporated into the food matrix, promoting and strengthening connections between the various components. It could be also attributed to diff erences in composition, resulting in a diff erent protein/fat/water ratio, which is a determining factor of the resulting gel consistency.…”
Section: Resultsmentioning
confidence: 99%
“…Worldwide market of functional food is dominated by gut health products particularly foods incorporated with probiotics (Cruz et al 2010). Probiotics are live microbial food supplements, several studies have shown that certain strains of bacteria belongs to genera Lactobacillus and Bifidobacterium confer health benefits such as control of diarrhoea, lactose intolerance, intestinal infections, immune system modulation and risk associated with carcinogenicity (Shah 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are live microbial food supplements, several studies have shown that certain strains of bacteria belongs to genera Lactobacillus and Bifidobacterium confer health benefits such as control of diarrhoea, lactose intolerance, intestinal infections, immune system modulation and risk associated with carcinogenicity (Shah 2007). In addition, the probiotic approach of directly introducing live cells as dietary supplements another possible way to promote the growth of probiotic bacteria is through supplementation with prebiotics (Cruz et al 2010). Prebiotics are non-digestible short chain carbohydrates (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In general, incorporating prebiotic ingredients into ice cream may have a greater influence on flavor and texture, compared to probiotics, which may affect primarily flavor (Cruz et al, 2010). The metabolism of the probiotic cultures can result in the production of components that might contribute negatively to the taste and aroma of the product (Mohammadi et al, 2011).…”
Section: Acceptability Testmentioning
confidence: 99%